Within-farm soil fertility gradients affect response of maize to fertilizer application in Western Kenya - Vanlauwe, Bernard; Tittonell, Pablo A.; Mukulama, J (Springer, 2007)
Different fields within a farm have been observed to have different soil fertility status and this may affect the response of a maize crop to applied N, P, and K fertiliser. A limiting nutrient trial was carried out at six farms each, in three districts of Western Kenya. In each of the farms, the following treatments were laid out in three fields with different soil fertility status at different distances from the homestead (close, mid-distance, remote fields): no inputs, application of NPK, NP, NK, or PK fertiliser (urea, triple super phosphate, KCl) to maize. Total soil N decreased at all sites with distance to the homestead (from 1.30 to 1.06 g kg?1), as did Olsen-P (from 10.5 to 2.3 mg kg?1). Grain yields in the no-input control plots reflected this decrease in soil fertility status with distance to the homestead (from 2.59 to 1.59 t ha?1). In the NPK treatments, however, this difference between field types disappeared (from 3.43 to 3.98 t ha?1), indicating that N and P are the major limiting nutrients in the target areas. Response to applied N was related to the soil total N content in Aludeka and Shinyalu, but not in Emuhaia, probably related to the high use of partially decomposed organic inputs with limited N availability. Consequently, response to applied N decreased with distance to the homestead in Aludeka (from 0.95 kg kg?1 relative yield to 0.55 kg kg?1) and Shinyalu (from 0.76 kg kg?1 to 0.47 kg kg?1), but not in Emuhaia (from 0.75 kg kg?1 to 0.68 kg kg?1). Response to applied P was related to the soil Olsen-P content at all sites. While for farms with a relatively high Olsen-P gradient, response to applied P decreased with distance to the homestead (from 0.99 kg kg?1 to 0.68 kg kg?1), large variability in Olsen-P gradients across field types among farms within a specific site often masked clear differences in response to P between field types for a specific site. Clear scope for field-specific fertiliser recommendations exists, provided these are based on local soil knowledge and diagnosis. Scenario analysis, using farm-scale modelling tools, could assist in determining optimum allocation strategies of scarcely available fertiliser for maximum fertiliser use efficiency.